ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (PPK-BLUD) PADA RSU CUT MEUTIA KABUPATEN ACEH UTARA - Cut Muftia Keumala; Maryana Maryana; Dasmi Husin; M. Lutfi Al Fahmi; Shalawati Shalawati; Shasqia Ulfa Tamara; Intan Zahara (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This study purpose to analyze the financial performance of the Cut Meutia General Hospital in North Aceh District before and after the implementation of the Regional Public Service Board Financial Management Pattern (PPK-BLUD) period of 2012-2019. The financial ratios used are profitability, liquidity, solvency and activity ratios. This study uses secondary data in the form of quantitative data, namely financial report data. Data analysis to test each variable using the normality test and paired sample t-test. The results showed that there were differences before and after PPK-BLUD in the ratios of profitability, liquidity and activity while the solvency ratios showed no statistically significant differences.